Internationalization of Higher Education: The Need for a More Ethical and Qualitative Approach - de Wit, Hans (Journal of International Students, 2020)
Universities have always had international dimensions in their research, teaching, and service to society, but those dimensions were in general more ad hoc, fragmented, and implicit than explicit and comprehensive. In the last decade of the previous century, the increasing globalization and regionalization of economies and societies, combined with the requirements of the knowledge economy and the end of the Cold War, created a context for a more strategic approach to internationalization in higher education. International organizations such as the Organisation for Economic Cooperation and Development, the United Nations Educational, Scientific and Cultural Organization, and the World Bank, national governments, the European Union, and higher education organizations such as the International Association of Universities placed internationalization at the top of the reform agenda. Internationalization became a key change agent in higher education, in the developed world but also in emerging and developing societies. Mobility of students, scholars, and programs; reputation and branding (manifested by global and regional rankings); and a shift in paradigm from cooperation to competition (van der Wende, 2001) have been the main manifestations of the agenda of internationalization in higher education over the past 30 years. International education has become an industry, a source of revenue and a means for enhanced reputation. Quantitative data about the number of international degree-seeking students, of international talents and scholars, of students going for credits abroad, of agreements and memoranda of understanding, as well as of co-authored international publications in high impact academic journals, have not only been key manifestations of this perception of internationalization, but also have driven its agenda and actions. This perception has resulted in an increasing dominance of English in research but also teaching, has createdthe emergence of a whole new industry around internationalization, has forced national governments to stimulate institutions of higher education going international, and hasgenerated new buzz words such as “cross-border delivery” and “soft power” in the higher education arena. In the period 2010–2020, we have seen not only the number of international students double to 5 million in the past decade, but also we have noticed an increase in franchise operations, articulation programs, branch campuses, and online delivery of higher education. There is fierce competition for talented international students and scholars, and immigration policies have shifted from low-skill to high-skill immigration. National excellence programs have increased differentiation in higher education with more attention for a small number of international world-class universities and national flagship institutions that compete for these talents, for positions in the global rankings, for access to high impact journals, and for funding, at the cost of other institutions. There is also an increasing concern about the neo-colonial dimension. In the current global-knowledge society, the concept of internationalization of higher education has itself become globalized, demanding further consideration of its impact on policy and practice as more countries and types of institution around the world engage in the process. Internationalization should no longer be considered in terms of a westernized, largely Anglo-Saxon, and predominantly English-speaking paradigm. (Jones & de Wit, 2014, p. 28) Internationalization became defined by the generally accepted definition of Knight (2008): “The process of integrating an international, intercultural or global dimension into the purpose, functions and delivery of post-secondary education,” describing clearly the process in a general and value neutral way. Some of the main trends in internationalization in the past 30 years have been: More focused on internationalization abroad than on internationalization at home More ad hoc, fragmented, and marginal than strategic, comprehensive, and central in policies More in the interest of a small, elite subset of students and faculty than focused on global and intercultural outcomes for all Directed by a constantly shifting range of political, economic, social/cultural, and educational rationales, with increasing focus on economic motivations Increasingly driven by national, regional, and global rankings Little alignment between the international dimensions of the three core functions of higher education: education, research, and service to society Primarily a strategic choice and focus of institutions of higher education, and less a priority of national governments Less important in emerging and developing economies, and more of a particular strategic concern among developed economies In the past decade, however, one can observe a reaction to these trends. While mobility is still the most dominant factor in internationalization policies worldwide, there is increasing attention being paid to internationalization of the curriculum at home. There is also a stronger call for comprehensive internationalization, which addresses all aspects of education in an integrated way. Although economic rationales and rankings still drive the agenda of internationalization, there is more emphasis now being placed on other motivations for internationalization. For example, attention is being paid to integrating international dimensions into tertiary education quality assurance mechanisms, institutional policies related to student learning outcomes, and the work of national and discipline-specific accreditation agencies (de Wit, 2019). Traditional values that have driven international activities in higher education in the past, such as exchange and cooperation, peace and mutual understanding, human capital development, and solidarity, although still present in the vocabulary of international education, have moved to the sideline in a push for competition, revenue, and reputation/branding. Around the change of the century, we observed a first response to these developments. The movement for Internationalization at Home within the European Union started in 1999 in Malmö, Sweden, drawing more attention to the 95% of nonmobile students not participating in the successful flagship program of the EU, ERASMUS. In the United Kingdom and Australia, a similar movement asked for attention to internationalization of the curriculum and teaching and learning in response to the increased focus on recruiting income-generating international students. And in the United States, attention emerged around internationalizing campuses and developing more comprehensive approaches to internationalization as an alternative for the marginal and fragmented focus on undergraduate study abroad on the one hand and international student recruitment on the other. These reactions were and are important manifestations of concern about the competitive, elitist, and market direction of internationalization, and are a call for more attention to the qualitative dimensions of internationalization, such as citizenship development, employability, and improvement of the quality of research, education, and service to society. A wide range of academic scholars and international education practitioners have pushed for change with their publications and presentations. A study for the European Parliament on the state of internationalization in higher education gave this push an extra dimension. Not only did the study provide a comprehensive overview of the literature and the practice of internationalization in higher education around the world, but also—based on a global Delphi Exercise—it promoted a new agenda for internationalization for the future, by extending the definition of Knight (2008), defining internationalization as follows: The intentional process of integrating an international, intercultural or global dimension into the purpose, functions and delivery of post-secondary education, in order to enhance the quality of education and research for all students and staff and to make a meaningful contribution to society. (de Wit et al., 2015) This definition gave a normative direction to the process by emphasizing that such a process does not proceed by itself but needs clear intentions, that internationalization is not a goal in itself but needs to be directed toward quality improvement, that it should not be of interest to a small elite group of mobile students and scholars but directed to all students and scholars, and that it should make a contribution to society. Over the past 5 years this new approach has received positive attention, and at the start of a new decade it is important to see if this shift back to a more ethical and qualitative approach with respect to internationalization is indeed taking place and what new dimensions one can observe in that shift.